CIRCULATING VYASA’S MAHABHARATA AS WORLD LITERATURE - Dian Windriani (JETA (Journal of English Teaching and Applied Linguistic), 2024)
This study explores how the Mahabharata has circulated globally through mechanisms such as translation, adaptation, canonization, and scholarly criticism. Drawing on qualitative research methods, this study examines the primary text of the Mahabharata and secondary data from academic journals, books, and critical theories. It highlights the role of translation in preserving the text’s cultural essence while navigating political and ideological challenges, particularly during British colonial rule. Adaptations of the Mahabharata, including its influence on Indonesian Wayang Kulit and Peter Brook’s international theater production, demonstrate the complex process of transforming the epic to suit diverse cultural contexts. The paper also addresses feminist readings of the epic, focusing on the representation of Draupadi, and how modern adaptations challenge traditional portrayals. By analyzing these mechanisms, this study reveals how the Mahabharata has been canonized, critiqued, and integrated into global literary discourse, affirming its enduring relevance and universal appeal.